Application of small amplitude oscillatory rheology measurements for estimating residual rennet activity in rennet whey. (November 2022) - Kayihura, Joseph F.; Huppertz, Thom; Vasiljevic, Todor
Abstract: The relationship between (very low) rennet activity (RA) levels and rennet coagulation time (RCT) is non-linear, and its determination is time consuming, with accuracy depending on an objective RCT. Here, RCT was determined by small amplitude oscillatory rheology and the Carlson, Hill and Olson's spiking technique was modified to estimate the unknown residual RA directly from a linear calibration curve of RCT against 1/RA created using the serum phase of the reconstituted skim milk (RSM) utilised for preparation of the rennet whey. The estimated residual RA mL −1 of the rennet whey could be obtained by spiking the rennet whey with a known RA derived from the linear range of the calibration curve. This observation was confirmed by a commonly used reverse-phase high-performance liquid chromatography (RP-HPLC) method. Using this information, a simple general model that estimates RA partitioning based on total volume of whey separated from the curd could be proposed.